The driving factors of Chinese aid allocation to African countries - Yushi Jiang; Dinkneh Gebre Borojo; Miao Miao; Xiaoyun Zhang (Cogent Business & Management, 2020)
We investigate the driving factors of Chinese aid allocation to 44 African countries for the periods 2003-2017. The Poisson pseudo-maximum likelihood (PPML) procedure is applied to estimate the gravity model of aid and loan allocation as it can solve zero-valued observations and heterogeneity problems prevalent in the panel data set. An aggregate indicator is derived for the quality of governance using principal component analysis. We controlled for aggregate Chinese aid and loans separately because a significant share of aid allocation China commits to African countries is repayable long-term loans. Controlling for source and destination countries' motives of aid and loan allocation, our findings provide evidence that Chinese aid and loan flow to African countries is significantly determined by African countries' and China's strategic, economic and commercial factors. The results further examine the importance of China-Africa trade and Chinese FDI, China's international support and foreign policy considerations in China's aid and loan allocation policy to African countries. Additionally, it gives a detailed analysis of the aid-institution paradox.
Keywords: 650; aid allocation; Poisson pseudo-maximum likelihood (PPML); gravity model; African countries; China